Emergency open cholecystectomy in a patient with severe aortic stenosis under epidural anaesthesia - Mishra, Roly; Sharma, Kritika; Mandal, Tapas; Panthakey, Harvesp; Mehta, Hemant (International Journal of Research in Medical Sciences, 2019)
Goldman and colleagues identified severe aortic stenosis (AS) as a risk factor for perioperative cardiac complications in non-cardiac surgery. Although patients with aortic stenosis are at an increased risk of perioperative cardiac events, they can undergo non-cardiac surgery relatively safely provided that the condition is recognized and appropriate monitoring and management put in place. The early detection and treatment of hypotension and arrhythmias are essential. We present a case of severe aortic stenosis posted for emergency open cholecystectomy which was successfully managed under epidural anaesthesia and had an uneventful recovery.